Pervasive crustal volcanic mush in the highly stretched sunda plate margin of northern Sumatra - Feng, Mingye (2024)
Arc volcanism, crustal deformation, and their interplay are poorly understood in northwestern Sumatra. Traditional receiver function H-κ stacking studies constrain the variations in crustal thickness and Vp/Vs ratio in volcanic zones but rarely estimate the melt fractions. Here, we propose a H-Φ stacking method, a variant of the H-κ stacking method, and apply it to the dense nodal array data from Aceh, northern Sumatra, to estimate crustal thickness, Vp/Vs ratio, and melt fraction. Most results show considerably high Vp/Vs ratios (∼1.98) and melt fractions (up to 19%), indicating pervasive crustal magmatic mush. The northwestern edge of the Aceh crust is much thinner (∼22 km) than extended crust globally, reflecting a highly stretched crust due to tectonic processes governing the opening of the Andaman Sea. This thin crust and high melt fractions explain the Bouguer gravity anomaly, and partly explain the northward migration of Quaternary volcanics.